(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
This study aims to describe learning difficulties in students of the Health and Recreational Health and Recreation program at the University of Nusa Cendana from a neuroscience point of view. This study uses a survey method. The data collection instrument in this study used a questionnaire and the results of the midterm exam questions. From the results of the study, it can be seen that students have difficulty learning statistics. This can be seen from the respondents’ answers to items 1, 2, and 11. It can also be seen from the midterm test scores obtained by students. Many behavioral and neuroimaging studies show that children are usually considered to have MLD if they show good math performance. weaker than a certain criterion level below the average performance on standardized mathematics achievement tests.